Ethnomathematics Exploration at the Grebeg Tape Tawaran Festival and Its Implementation in Elementary Mathematics Learning - Fadiana, Mu'jizatin; Ismarini, Yuninta Ulfa (Yayasan Corolla Education Centre, 2025)
This research aims to explore the concept of ethnomathematics in the Grebeg Tape Tawaran festival in the Kenduruan District, Tuban Regency, and its application in mathematics learning in elementary schools. Ethnomathematics is a learning approach used to help students integrate culture with mathematics learning. This research includes qualitative research with a type of field research. Data was collected through observation, interviews, and documentation. The research subjects were residents of Tawaran Village. Data collection techniques include direct observation and interviews. The results of the research show that the Grebeg Tape Tawaran festival contains many mathematical concepts that are relevant for elementary school learning. The shape of a mountain of tape resembling a cone can be used to teach the concept of spatial shapes and measurements. In addition, the tape creation process includes the concepts of comparison, arithmetic, and time measurement. Implementing the results of ethnomathematics exploration can enrich mathematics learning resources in elementary schools by integrating local culture so that learning becomes more meaningful and interesting for students.